Comments on “Buckling behavior of a graphite/epoxy composite plate under parabolic variation of axial loads” - Bambill, Diana Virginia (2005)
COMMENT ON Hu H, Badiz A, Abatan A. Buckling behavior of a graphite/epoxy composite plate under parabolic variation of axial loads. International Journal of Mechanical Sciences 2003;45:1135–47.